THE RELATIONSHIP BETWEEN DYNAMIC STABILITY AND SHOOTING ACCURACY IN STATIONARY AND MOVING CONDITIONS AMONG ADVANCED SOCCER PLAYERS - Al-Baitar, Layth Muthanna Ibrahim; Abdulmaged, Mustafa Ahmed; Ahmed, Alaa Hashim; Salim, Salim Saad (Journal Olahraga Rekat (Rekreasi Masyarakat), 2025)
Background. Football is one of the most popular sports in the world in terms of the number of spectators and the level of physical and technical proficiency required. In football, the main objective is to score as many goals as possible during the game. Objectives. The study aims to explore the relationship between dynamic stability and shooting accuracy in stationary and moving conditions among advanced soccer players in the city of Samarra, Iraq. Method. This study used a descriptive-analytical method with a correlational design. The study consisted of 54 participants, chosen from premier football teams in Iraq. Two tests were conducted in the field to assess the accuracy of shooting in stationary and movement situations. Results. The study found that the accuracy of shooting in stationary situations is significantly higher than in movement situations. On the other hand, the study found that the accuracy of shooting is significantly influenced by knee angle, contact time, center of mass deviation, and trunk oscillation in both stationary and movement situations, whereas ankle angle and execution time are significantly influenced in movement situations only. The study also found that the proposed model is able to explain 58% and 64% of the total variance in shooting accuracy in stationary and movement situations, respectively, using multiple regression analysis, whereas the results showed statistically significant differences in favor of stationary shooting using repeated-measure ANOVA. Conclusion. The study concluded that the accuracy of shooting is significantly influenced by dynamic balance, and this is an important factor in the accuracy of shooting in soccer games. In addition, the study also found that the use of Kenova software in the Iraqi sports arena is effective in producing reliable results, which can be used by coaches in improving the accuracy of shooting in soccer players.